How do Detergents Work? A Qualitative Assay to Measure Amylase Activity. Issue 3 (2nd July 2016) - Novo, M. Teresa; Casanoves, Marina; Garcia-Vallvé, Santi; Pujadas, Gerard; Mulero, Miquel; Valls, Cristina
Abstract : We present a practical activity focusing on two main goals: to give learners the opportunity to experience how the scientific method works and to increase their knowledge about enzymes in everyday situations. The exercise consists of determining the amylase activity of commercial detergents. The methodology is based on a qualitative assay using a colorimetric process. Quantitative results are also obtained by measuring the halo formed. This activity is suitable for and adaptable to learners at different levels of education: primary school, secondary education or even for pre-service teachers, which is the group the version described in this paper was intended for. This laboratory activity was designed to include the scientific method as a learning outcome. This was especially important in pre-service teachers, as increasing scientific literacy is one of the primary goals of science education. Through the activity, students also learn about micro-organisms and their applications in their daily lives, which is one of the tenets of Science–Technology–Society–Environment programs. A case study was conducted with a group of learners made up of 75 pre-service teachers from Universitat Rovira i Virgili in Tarragona, in order to verify whether this lab activity is well designed and can be satisfactorily implemented.